2019
DOI: 10.1002/mrd.23289
|View full text |Cite
|
Sign up to set email alerts
|

A putative protein–RNA complex regulates posttranscriptional processing of cytochrome P450 aromatase (CYP19A1) in bovine granulosa cells

Abstract: Follicle growth and granulosa cell health are dependent on the secretion of estradiol from granulosa cells. Estradiol is synthesized from androgen precursor by cytochrome P450 aromatase (CYP19A1), and in cattle CYP19A1 messenger RNA has a short half‐life but a long (3.5 kb) 3′‐untranslated region (3′UTR), suggesting that posttranscriptional regulation may be important for control of enzyme activity. We tested this hypothesis by inserting the CYP19A1 3′UTR and fragments thereof into a reporter vector between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…One of the major characteristics is that the synthesis of estradiol by granulosa cells is related to follicle development, oocyte maturation, ovulation and inhibiting granulosa cell apoptosis [64,68]. Interestingly, the present results showed that milk-derived exosomes could promote the secretion of estradiol and progesterone in bovine granulosa cells.…”
Section: Discussionmentioning
confidence: 49%
“…One of the major characteristics is that the synthesis of estradiol by granulosa cells is related to follicle development, oocyte maturation, ovulation and inhibiting granulosa cell apoptosis [64,68]. Interestingly, the present results showed that milk-derived exosomes could promote the secretion of estradiol and progesterone in bovine granulosa cells.…”
Section: Discussionmentioning
confidence: 49%
“…tuberculosis bacilli and for the diagnosis of active TB [92]. RNA has a short half-life [93] and it is predicted to be found in only viable cells. In addition, M.…”
Section: Detection Of M Tuberculosismentioning
confidence: 99%
“…To minimize this possibility, real-time mRNA-based quantitative (q)RT-PCR, instead of DNA, might be useful to detect viable M. tuberculosis bacilli and for the diagnosis of active TB [ 92 ]. RNA has a short half-life [ 93 ] and it is predicted to be found in only viable cells. In addition, M. tuberculosis mRNA is quite stable, with a half-life of roughly 9 min [ 94 ].…”
Section: Detection Of M Tuberculosismentioning
confidence: 99%
“…One of the major characteristics is that the estradiol level within the dominant follicles and potential ovulatory follicles is higher compared with that of subordinate follicles and atretic follicles ( Ireland & Roche, 1982 ; Ireland & Roche, 1983 ). Estradiol synthesized by CYP19A1 in granulosa cells is related to follicle maturation and is essential for follicle development, ovulation, and inhibiting granulosa cell apoptosis ( Sahmi et al, 2019 ; Okamoto et al, 2016 ). In addition, inhibins, a negative feedback of FSH secretion, suppress the further development of follicles through the pituitary-gonadal system ( Xu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%